Thinking Preference Awareness, Leadership Skills and Learning Behaviour - Boyko-Head, Christine (International Journal for Talent Development and Creativity, 2021)
Prior to Covid-19, studies identified a gap between the skills employers needed and the skills graduates had (IBM, 2012, 2016, WEF2016b). Still impacted by the pandemic, graduating classes of the future may not be any different. This paper shares findings from an Applied Research in Innovation and Education (ARIE) pilot project conducted between 2016-2017 at Mohawk College, Ontario Canada with 117 students enrolled in a 14week, mandatory Communications course. Specifically, the pilot project explored perceptions of leadership, employability skills and attributes in post-secondary students and how they perceived and assessed their leadership skills and developmental needs for future employment. The study also examined how learner awareness of their own and others thinking preferences when problem-solving impacted their academic behaviours and development goals. The aim was to determine the impact thinking preference awareness in learners might have on their communication, collaboration, and development of personal and professional learning targets. Using a mixed-methods, transformative-emancipatory critical approach, the research highlights the classroom as a living laboratory rich in emergent research questions and revealed additional areas of research regarding thinking preference theory and language, self-differentiated learning and inclusive, learner-focused curriculum design.